Can the kinesio taping change the pelvic tilt angle in healthy young women? - Peixoto, Jennifer Granja; Borel, Wyngrid Porfirio; Avelino, Patrick Roberto; Silva, Marina Ribeiro; Rocha, Gerdeany Mendes da; Teixeira-Salmela, Luci Fuscaldi (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: The pelvis is a key structure for the alignment of the body and its misalignment can cause pain. Weakness of the gluteus maximus (GM) muscle can increase the pelvic tilt angle (PTA). Kinesio Taping (KT) is a technique used to stimulate muscular action, by applying a bandage over the muscle with a longitudinal tension of 25% to 35%. Objectives: To assess the immediate effects of the KT stimulating technique over the GM on the PTA of healthy women and verify if the 60% tension would lead to better results. Methods: Twenty-six healthy women, with a mean age of 23.3±2.8 years, had their PTA bilaterally assessed by means of computerized photogrammetry before and immediately after received KT application with 30 and 60% tensions. Repeated measure ANOVA (2x2) was used to assess the main and interaction effects between the applied tensions and time. The standard error of the measurement (SEM) was also calculated to evaluate the clinical impact of the techniques. Results: The analysis revealed that both KT tensions reduced the PTA. Although no significant differences were observed between the two employed tensions, the clinical effects were higher for the 60% tension. Conclusion: Both applied KT tensions reduced the PTA in the standing position of healthy young women, but the tension of 60% led to more clinically significant results.